Acrylonitrile Modified Glycidyl Methacrylate/ MethylmethacrylateTerpolymer: A Novel Carrier for Enzyme Immobilization - Srivastava, Sangeeta; Malshe, V.C.; Dave, M.A. (Asian Journal of Chemistry, 2010)
In this study, a new carrier (i.e., the poly(acrylonitrile/glycidyl methacrylate/methylmethacrylate copolymer beads) for enzyme immobilization is evaluated. Two different types of copolymer beads with different swellabilities with an average diameter of about 200 μm were produced by suspension copolymerization of the respective co-monomers, with or without using cyclohexanone. BPO and PVA were used as the initiator and the stabilizer. The copolymer beads produced without cyclohexanol were non-porous and non-swellable, while porous and swellable (swelling ratio: 14.28%) beads were obtained in which cyclohexanol was used as the porogen. Immobilization of a model enzyme (i.e., glucose oxidase) was studied to show the feasibility of using these beads as an enzyme carrier. More enzymes, but with very low activities, were immobilized on the beads with relatively lower swellabilities, while much higher activities were observed on the beads with relatively higher swellabilities prepared with cyclohexanol. Invertase (from Bio-con India) was immobilized on to a copolymer of glycidyl methacrylate and methyl methacrylate. Polymer particles having glycidyl ether groups were prepared through suspension polymerization in aqueous medium, addition of acrylonitrile provides sufficient space for enzyme immobilization. From the HCldioxane back titration method, it was found that about 8–10% of oxirane oxygen remained on the final particles. Invertase ‘immobilized’ on copolymer exhibited complete inversion of sucrose at neutral pH and 30–37ºC. The prepared immobilized invertase could completely hydrolyze sucrose in water at room temperature, at an enzyme concentration of 0.2% based on sucrose weight having invertase activity 1,00,000 U/mL. The enzyme preparation was stable under stirred conditions and could be reused multiple times without loss of enzyme activity. It was found that the nature of the polymer used for enzyme conjugation had a significant effect on the activity of the invertase used.